Biodegradable microparticulate drug delivery system of diltiazem HCl - Manish Kumar Gupta (Brazilian Journal of Pharmaceutical Sciences, 2012)
The efficacy of a drug in a specific application requires the maintenance of appropriate drug blood level concentration during a prolonged period of time. Controlled release delivery is available for many routes of administration and offers many advantages (as microparticles and nanoparticles) over immediate release delivery. These advantages include reduced dosing frequency, better therapeutic control, fewer side effects, and, consequently, these dosage forms are well accepted by patients. Advances in polymer material science, particle engineering design, manufacture, and nanotechnology have led the way to the introduction of several marketed controlled release products and several more are in pre-clinical and clinical development. The objective of this work is to prepare and evaluate diltiazem HCl loaded albumin microparticles using a factorial design. Albumin (natural polymer) microparticles were prepared by emulsion heat-stabilization method. Selected formulations were characterized for their entrapment efficiency, particle size, surface morphology, and release behavior. Analysis of variance for entrapment efficiency indicates that entrapment efficiency is best fitted to a response surface linear model. Surface morphology was studied by scanning electron microscopy. Scanning electron microscopy of the microparticles revealed a spherical, nonporous and uniform appearance, with a smooth surface. The geometric mean diameter of the microparticles was found to be 2-9 µm, which more than 75% were below 3.5 µm and drug incorporation efficiency of 59.74 to 72.48% (w/w). In vitro release profile for formulations containing diltiazem HCl loaded BSA microparticles with heat stabilization technique shows slow controlled the release of the drug up to 24 hours. The release pattern was biphasic, characterized by an initial burst effect followed by a slow release. All selected microparticles exhibited a prolonged release for almost 24 hours. On comparing regression-coefficient (r²) values for Hixson Crowel, Higuchi and Peppas kinetic models, different batches of microparticles showed Fickian, non-Fickian, and diffusion kinetics. The release mechanism was regulated by D:P ratio. From the statistical analysis it was observed that as the drug:polymer (D:P) ratio increased, there was a significant increase in the encapsulation efficiency. Based on the particle size, entrapment efficiency and physical appearance, DTM-3 formulations were selected for in vivo release study and stability study. The in vivo result of drug loaded microparticles showed preferential drug targeting to liver followed by lungs, kidneys and spleen. Stability studies showed that maximum drug content and closest in vitro release to initial data were found in the formulation stored at 4 ºC. In present study, diltiazem HCl loaded BSA microparticles were prepared and targeted to various organs to satisfactory level and were found to be stable at 4 ºC. A eficácia terapêutica de um fármaco depende da manutenção de seu nível plasmático adequado em determinado intervalo de tempo. Nesse sentido, a liberação modificada de fármacos está disponível em muitas vias de administração e oferece muitas vantagens (como micropartículas e nanopartículas) quando comparada às formulações de liberação imediata. Essas vantagens incluem reduzida frequência da dosagem, melhor controle terapêutico e menos efeitos colaterais. Assim sendo, esses produtos apresentam maior aceitação pelos pacientes. Os avanços na ciência dos materiais, na engenharia das partículas, em manufatura e em nanotecnologia permitiram a introdução no mercado de vários produtos de liberação modificada e vários outros se encontram em desenvolvimento pré-clínico e clínico. O objetivo do presente trabalho foi preparar e avaliar o fármaco cloridrato de diltiazem associado a micropartículas de albumina utilizando planejamento fatorial. As micropartículas de albumina, um polímero natural, foram preparadas por método de emulsão empregando estabilização por calor. As formulações selecionadas foram caracterizadas no que se refere à sua eficiência de encapsulamento, tamanho médio de partículas, morfologia de superfície e perfil de liberação do fármaco. A análise de variância relativa à eficiência de encapsulamento indicou superfície de resposta linear. Com referência à morfologia superficial, essa foi avaliada empregando microscopia eletrônica de varredura. Essa análise revelou micropartículas esféricas, não porosas e de aparência uniforme, com superfície lisa. O diâmetro médio das micropartículas foi entre 2 e 9 µm, sendo que mais de 75% das micropartículas se apresentaram abaixo de 3,5 µm. Além disso, a eficiência de encapsulamento foi entre 59,74 e 72,48%. Quanto ao ensaio para avaliação do perfil de liberação in vitro do fármaco associado às micropartículas, as formulações apresentaram liberação lenta até 24 horas. O comportamento foi caracterizado por liberação inicial (efeito burst) seguida por liberação lenta. Todas as fórmulas selecionadas apresentaram liberação prolongada por aproximadamente 24 horas. Na comparação entre os valores de coeficientes de regressão (R²), os modelos propostos por Hixson Crowel, Higuchi e Peppas, para diferentes formulações de micropartículas, demonstraram cinética de liberação de acordo com modelo Fickiano e não-Fickiano. O mecanismo de liberação do fármaco foi regulado pela razão entre o fármaco e o polímero. A análise estatística revelou significativo aumento da eficiência de encapsulamento quando essa razão aumentou. As avaliações relativas à análise dimensional das micropartículas, à eficiência de encapsulamento do fármaco e à morfologia permitiram a seleção da formulação DTM-3 para os ensaios de liberação in vivo e para o estudo da estabilidade. O ensaio de liberação in vivo do fármaco associado às micropartículas demonstrou sítio-alvo preferencial no fígado, seguido pelos pulmões rins e baço. No presente estudo, as micropartículas de albumina contendo cloridrato de diltiazem foram adequadamente preparadas e orientadas satisfatoriamente para vários órgãos. Além disso, a formulação selecionada apresentou estabilidade físico-química a 4 ºC.